2021
DOI: 10.1002/pat.5226
|View full text |Cite
|
Sign up to set email alerts
|

Identification of voids and interlaminar shear strengths of polymer‐matrix composites by optical microscopy experiment and deep learning methodology

Abstract: The internal void defects induced during the manufacturing process of polymer‐matrix composites can significantly degrade the mechanical properties of the composite, particularly the interlaminar shear strength (ILSS). In this study, we developed an innovative integrated methodology based on a deep learning semantic segmentation algorithm, named DeepLabV3+, and a theoretically driven equation to automatically identify voids in optical images and investigate the relationship between the microscopic voids and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
3
5
0
Order By: Relevance
“…Nevertheless, the void sizes obtained for all laminate types in our dataset are in agreement with the range of void sizes found in the literature [21,23]. Moreover, plotting the frequency measures of void sizes into an histogram, for each laminate type, it can be observed that the distribution of void sizes follows a Weibull distribution ( Figures 10,11,12), which is also consistent with the reported literature [47].…”
Section: Datasetsupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, the void sizes obtained for all laminate types in our dataset are in agreement with the range of void sizes found in the literature [21,23]. Moreover, plotting the frequency measures of void sizes into an histogram, for each laminate type, it can be observed that the distribution of void sizes follows a Weibull distribution ( Figures 10,11,12), which is also consistent with the reported literature [47].…”
Section: Datasetsupporting
confidence: 92%
“…Usually, microscopy and X-ray micro-CT techniques are reported to provide a good level of detail, which enables the accurate measurement and parametrization of void characteristics on the smaller length scales [20,22,23]. Due to its simplicity, lower cost and reasonable accuracy and detail, optical microscopy is still a commonly employed imaging technique to conduct void content analyses [1,4,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Voids are the most common type of defects induced by the residual air during the manufacturing process of composites [ 1 ], which significantly affect the hygrothermal aging performances of composites by altering the stress field and moisture field [ 2 , 3 ]. Particularly, void defects are highly sensitive to the moisture under the hygrothermal environment, and they can further decrease the matrix-dominated properties, which can ultimately reduce the service life of composite structures [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, supervised (mostly CNN) approaches are excelling in this job in contrast, fluorescence, and super-resolution microscopy, among others. 502–510 For that, the idea we have widely reviewed on simulating data that resembles the variability of our target micrographs is also valid here. For instance, A. Sekh et al followed the idea of physics-based labelling by simulating fluorescence microscopy images out of the simulated 3D geometries of organelles (Fig.…”
Section: Inspirations From Other Fields For Future Developmentsmentioning
confidence: 93%